Choreographing the Double Strand Break Response: Ubiquitin and SUMO Control of Nuclear Architecture - Harding, Shane M.; Greenberg, Roger A. (Frontiers in Genetics, 2016)
The cellular response to DNA double strand breaks (DSBs) is a multifaceted signaling program that centers on post-translational modifications including phosphorylation, ubiquitylation and SUMOylation. In this review we discuss how ubiquitin and SUMO orchestrate the recognition of DSBs and explore how this influences chromatin organization. We discuss functional outcomes of this response including transcriptional silencing and how pre-existing chromatin states may control the DSB response and the maintenance of genomic stability.